2013
DOI: 10.1371/journal.pone.0063298
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Activates the β-catenin Pathway to Cause Intestinal Neoplasia

Abstract: Colonic bacteria have been implicated in the development of colon cancer. We have previously demonstrated that toll-like receptor 4 (TLR4), the receptor for bacterial lipopolysaccharide (LPS), is over-expressed in humans with colitis-associated cancer. Genetic epidemiologic data support a role for TLR4 in sporadic colorectal cancer (CRC) as well, with over-expression favoring more aggressive disease. The goal of our study was to determine whether TLR4 played a role as a tumor promoter in sporadic colon cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 63 publications
4
87
0
1
Order By: Relevance
“…Our results are in agreement with previous studies showing that TLR4 is involved in colon cancer growth (5,(13)(14)(15)45). We concluded that the anticancer effect of eritoran in in vivo animal models is predominantly via direct actions on tumorous epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with previous studies showing that TLR4 is involved in colon cancer growth (5,(13)(14)(15)45). We concluded that the anticancer effect of eritoran in in vivo animal models is predominantly via direct actions on tumorous epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidence suggests that LPS receptors are involved in the dysregulation of epithelial apoptosis and proliferation that predisposes the tissue of the colon to tumorigenesis. Previous animal studies have indicated that TLR4/ MyD88 signaling causes tumor cell hyperproliferation via pathways dependent on cyclooxygenase (COX), EGFR, and b-catenin (5,(13)(14)(15). In vitro studies have shown a direct effect of LPS via TLR4/MD2 signaling on the stimulation of intestinal epithelial cell proliferation and a resistance to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the observation that overexpression of TLR4 in intestinal epithelial cells results in increases in Lgr5 ϩ cell number and proliferation (17). Although the role of TLR4 activation in normal small intestinal growth has not been previously addressed, TLR4 signaling is required for the enhanced colonic epithelial response seen in the repair of DSS colitis (2,6,14).…”
Section: Discussionsupporting
confidence: 88%
“…The cell concentration was determined using the Sysmex XT-4000i hematology analyzer (Sysmex, Kobe, Japan). PBMCs were cultured in 24 well-plates and each well consisted of RPMI 1640 medium supplemented with 10% fetal calf serum (Invitrogen Life Technologies), 10 6 PBMCs and the respective agonist. Following incubation for 24 h in an SS-23062 carbon dioxide incubator (SHEL LAB, Cornelius, OR, USA) with 5% CO 2 , the supernatant was harvested, and TNF-α and IL-1β were measured using the IMMULITE 1000 immunoassay system (Siemens Healthcare Diagnostics, Erlangen, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Each sub-type is able to recognize a specific ligand. For example, TLR2 recognizes peptidoglycan (PGN) (5) and TLR4 recognizes lipopolysaccharide (LPS) (6). After recognizing specific ligands, TLRs signal through myeloid differentiation factor (MyD)88-dependent or -independent pathways.…”
Section: Introductionmentioning
confidence: 99%